1998
DOI: 10.1177/156482659801900409
|View full text |Cite
|
Sign up to set email alerts
|

The Helen Keller International Food-Frequency Method Underestimates Vitamin A Intake Where Sustained Breastfeeding is Common

Abstract: A recent innovation in assessing community vitamin A status is the Helen Keller International food-frequency method, which is based on weekly intakes of key foods among pre-school children. Since it excludes breastmilk, we investigated whether the amount of breastmilk received by 40 children aged one to three years in a rural area of Bangladesh contributed significantly to their vitamin A intake. Vitamin A intake was indirectly calculated from the consumption of breastmilk, which was quantified over a 9-hour p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…The paper in this issue, "The Helen Keller International food-frequency method underestimates vitamin A intake where sustained breastfeeding is common," reports that even evaluation of a method in three different countries was apparently not sufficient to ensure its applicability to all countries [7].…”
Section: Commentarymentioning
confidence: 99%
“…The paper in this issue, "The Helen Keller International food-frequency method underestimates vitamin A intake where sustained breastfeeding is common," reports that even evaluation of a method in three different countries was apparently not sufficient to ensure its applicability to all countries [7].…”
Section: Commentarymentioning
confidence: 99%
“…A questionnaire was developed based on the Helen Keller International Food Frequency Method [12] to obtain information about consumption frequency of vitamin A dietary and meat intake in a week before the interview. The pre-tested questionnaire was administered by trained interviewers at each site.…”
Section: Study Methodsmentioning
confidence: 99%
“…According to the de¿ nitions in China and abroad, [8,9,12,15] 6.9% of the children had sub-clinical VAD and 33.7% had suspected sub-clinical VAD. The mean value of serum retinol was 31.5 ȝg/dl.…”
Section: Vad In Beijing and Guizhoumentioning
confidence: 99%
“…The HKI FFM was shown valid for identifying VA deficiency in a few countries, although it had a high false positive rate (Sloan et al, 1997). Critics showed that it may underestimate VA intake if sustained breastfeeding is common and if milk is a normal dietary component, as neither breast or other milk is reflected in the scores (Persson et al, 1998(Persson et al, , 1999. Due to findings that provitamin A carotenoid bioavailability is less than was once thought, the method of calculating the score now no longer reflects current conversion factors 3 (de Pee et al, 1998;Institute of Medicine, 2001).…”
Section: Introductionmentioning
confidence: 97%